EFEKTIVITAS MEDIA WORDWALL DALAM MENINGKATKAN PENGUASAAN QAWA’ID PADA SISWA MA DARUL ULUM TLASIH TULANGAN SIDOARJO - Nia Fatma Safitri; Najih Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the wordwall media in improvingstudents’ mastery of qawa’id (arabic grammar) among 10th-grade students at MADarul Ulum Tulangan Sidoarjo. The problem identified is the students’ lowcomprehension of qawa’id due to the reliance on conventional teaching methodsand the lack of engaging media. A quantitative research method was employedusing a pre-experimental design (One-Group Pre-Test Post-Test Design) involving31 students selected through a census sampling technique. Research instrumentsincluded tests (pre-test and post-test), interviews, observations, and documentation.The wordwall media used consisted of quiz, unjumble, and open the box formats.The descriptive statistical analysis showed a significant improvement in students’learning outcomes, with an average pre-test score of 40.94 and a post-test score of89.65. The paired sample t-test revealed a significance value (2-tailed) of 0.000 (<0.05), indicating a statistically significant difference before and after using thewordwall media. Therefore, it can be concluded that wordwall is effective inenhancing students’ mastery of qawa’id.